The Friendship Bench as a brief psychological intervention with peer support in rural Zimbabwean women: a mixed methods pilot evaluation. (26th August 2021) - Fernando, Shamiso; Brown, Tim; Datta, Kavita; Chidhanguro, Dzivaidzo; Tavengwa, Naume V.; Chandna, Jaya; Munetsi, Epiphania; Dzapasi, Lloyd; Nyachowe, Chandiwana; Mutasa, Batsirai; Chasekwa, Bernard; Ntozini, Robert; et al.
Abstract: Background: There is a large treatment gap for common mental disorders in rural areas of low-income countries. We tested the Friendship Bench as a brief psychological intervention delivered by village health workers (VHWs) in rural Zimbabwe. Methods: Rural women identified with depression in a previous trial received weekly home-based problem-solving therapy from VHWs for 6 weeks, and joined a peer-support group. Depression was assessed using the Edinburgh Postnatal Depression Scale (EPDS) and Shona Symptom Questionnaire (SSQ). Acceptability was explored through in-depth interviews and focus group discussions. The proportion of women with depression pre- and post-intervention was compared using McNemar's test. Results: Ten VHWs delivered problem-solving therapy to 27 women of mean age 33 years; 25 completed six sessions. Women valued an established and trustful relationship with their VHW, which ensured confidentiality and prevented gossip, and reported finding individual problem-solving therapy beneficial. Peer-support meetings provided space to share problems, solutions and skills. The proportion of women with depression or suicidal ideation on the EPDS declined from 68% to 12% [difference 56% (95% confidence interval (CI) 27.0–85.0); p = 0.001], and the proportion scoring high (>7) on the SSQ declined from 52% to 4% [difference 48% (95% CI 24.4–71.6); p < 0.001] after the 6-week intervention. Conclusion: VHW-delivered problem-solving therapy and peer-support was acceptable and showed promising results in this pilot evaluation, leading to quantitative and qualitative improvements in mental health among rural Zimbabwean women. Scale-up of the Friendship Bench in rural areas would help close the treatment gap for common mental disorders.